Persistence and occurrences of bacteria on wastewaterin selected treatment plant of UiTM Pahang branch,Jengka Campus / Zulhafizal Othman ... [et al.] - Othman, Zulhafizal; Muhamad, Noor Safwan; Mohd Latib, Farah Wahida; Bachok, Mohd Fairuz (Universiti Teknologi MARA Cawangan Pahang, 2019)
Coliform bacteria are present in the environment and feces of all warm-blooded animals and humans. Fecal coliform bacteria are a subgroup of total coliform bacteria. They exist in the intestines and feces of people and animals. E. coli is a subgroup of the fecal coliform group. Human or animal feces infected with E. coli sometimes get into lakes, pools, and water supplies. This research is conducted to identify the occurrence of the bacteria in influent and effluent of wastewater discharged from selected treatment plant in Universiti Teknologi MARA (UiTM) Pahang. The samples were taken and preserved before further analysis. The method used in this experiment is presumptive total coliform test using m-Endo broth (MF). MF Method is a fast and simple way to estimate bacterial populations by passing an appropriate sample volume through a membrane filter (0.45 microns) small enough to retain the bacteria present. Several samples were tested and the result showed that the bacteria (total coliform bacteria) are persistence in the sample and further discussion have been done by referring to the Water Quality Index from Department of Environment, Malaysia